Crossing Borders : International Studies for the 21st Century - Chernotsky, Harry Ira; Hobbs, Heidi H. (London Sage Publications, 2016)
This introductory text offers a clear, compelling framework for understanding the global forces that both unite and separate world citizens - looking at types of borders and then delving into extended case study chapters to explore the specific challenges they pose.
Include Tables, Figures, Maps, Notes and Index.
International Studies for the 21st Century.
Keywords: International relations -- Security, International -- Technological innovations--Economic aspects